Corrosion Rate of Sand Blasted and Acid Etched Ti6Al4V for Dental Implants. (2015) - Strnad, Gabriela; Chirila, Nicolae
Abstract: The aim of present research was to find an effective method to manufacture sand blasted and acid etched (SLA) Ti6Al4 V surfaces for dental implants, with an average surface roughness Ra of 1...2 μm and a proper surface topography, as the morphology of dental implant surface is of extreme importance in the process of implant osseointegration. Several disc samples were subjected to sand blasting with 250...300 μm SiO2 large grits followed by different procedures of acid etching using sulfuric acid and hydrochloric acid (single acid baths, dual acid bath), at room temperature and elevated temperature (60°). Corrosion rate and corrosion penetration rate were calculated from weight loss. The Ra roughness of samples was measured in each stage of the process. Scanning electron microscopy was performed in order to characterize the topography of the surfaces. We found that a proper SLA surface, with a roughness Ra of 2 μm, and a topography with micropits less than 10 μm, can be obtain by sand blasting the machined surface with large grits and then acid etching it using a mixture of (H2 SO4 +HCl) (1:1) at 60 °C, for 24 hours.